Exploring the mechanism and component basis of Naja naja (Snake) venom for the treatment of cancer by network pharmacology and molecular docking techniques - LEELA SUDARSANAN AMULYA; THAMILARASAN MANIVASAGAM; RAVI SURYA; PANDIAN SUBASRI; AROKIASAMY JUSTIN THENMOZHI (The Bioscan, 2025)
Background: Numerous experimental models proved the protective effect of Naja naja snake venom on various cancers. However, their mechanism of action is not known. In the present study, network pharmacology and molecular docking technology were performed to analyse the molecular mechanism of components of Naja naja for the treatment of cancer. Methods: The venom peptide structures were obtained from pubchem databases and RCSB PDB. The targets of snake venom peptides were obtained from literature survey. The protein-protein interaction network was done using the STRING webtool and ShinyGo 0.80 software. The binding affinity between potential targets and active compounds was evaluated by molecular docking using Autodock vina. Result: By analysing string programme, the highest degree of protein interaction was found between AChE and metelloprotease and the proteins of antioxidant, apoptotic, clock and inflammation, implying that these enzymes may exert its anti-cancer action through the regulation of the above said pathways. Conclusion: It is difficult to find the therapeutic target of all snake peptides/protein, because the structures for most of them are not available. So, in this study, we explored the molecular target of few snake venom peptides/proteins using string analysis and studied the structure-function relationships of snake venom peptides. This in silico experiment will paved a way for designing preclinical and clinical experiments.